4x + 3 doesn't factor. It is in its simplest form.
0.25
0.1053
4x-26 = -22
If the equation is y = 4x + 8, then the standard form is 4x - y + 8 = 0
(5/x) * (3/4) = (5*3)/(x*4) = 15/4x
4x
5x x 4x = 20x^2 5x + x + 4x = 10x
4x + 3 doesn't factor. It is in its simplest form.
85
0.25
0.1053
8+4x
If the equation is -4x + 2 = 26, then you can solve like so: -4x + 2 = 26 -4x = 26 - 2 = 24 4x = -24 x = -6 Check: -6 * -4 = 24, 24 + 2 = 26
-20 = -4x +6 add 20 to both sides 0 = -4x +26 4x = 26 x = 26/4 = 6.5
It is -4x -96.
If I understand your question exactly as it is phrased you are making two statements: 1)Width= X 2)Length= 4X So... Length= (Width times 4) Multiply the width by 4 and you have the length. Or in its simplest form: 4X